The Battle at Mamusa The Western Transvaal border culture and the ethno-dissolution of the last functioning Korana polity - Erasmus, Piet (UJ Press, 2015)
The Battle of Mamusa reflects the grievous event in the Western Transvaal border culture context that contributed profoundly to the dissolution of the last functioning Korana polity. The narrative presented in this work is exceptional for at least two reasons: Firstly, for the thoughtful manner in which the intriguing concept of metaphors is applied in this study of historical ethnography cum ethnohistory. Secondly, for the skilful way in which the author relates the battle of Mamusa to how present-day Korana and neo- Khoisan communities, in a new context, are relating to their future in a post-1994 constitutional dispensation. Prof. Henry C (Jatti) Bredekamp University of the Western Cape